Determination of activation energies of formic acid decomposition on the (100) surface of palladium catalysts. - Yue, Clarence Meng Yi. (2010)
The decomposition of formic acid (HCOOH), specifically the C-H and O-H bond cleavage was studied by density functional calculations on the (100) surface of singlemetal Pd. The NEB method was utilized to determine the TS structures for the decomposition reactions, and this method was tested using a set of two reactions, namely, H2 and OH decomposition, which are well studied as part of the Water-Gas Shift reactions. We obtained activation energies for the H2 and OH decomposition reactions, and the O-H bond cleavage for HCOOH decomposition – the values are Ea = -25 kJ/mol, 97 kJ/mol and 44 kJ/mol respectively. We expected the O-H bond cleavage to occur quicker for the HCOOH decomposition than for the OH decomposition because of the thermo-neutrality (DrxnE = -1 kJ/mol) of the OH decomposition reaction as compared to the moderately exothermic (DrxnE = -51 kJ/mol) HCOOH decomposition reaction.